Formation and development of psychologism in literature - Ступницька, Наталія Миколаївна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2019)
The opinions of researchers about the problem of artistic psychology are systematized and analyzed. Modern tendencies of social development substantially actualize the aspects of reflection of the external world through the prism of moral and ethical beliefs of the individual. It is determined the necessity in deeper theoretical approach to the study of the problem of artistic psychologism in literary studies. The text of the article deals with the peculiarities of the origin and development of psychologism, the specifics of the embodiment of human experiences in the pages of literary works of different epochs. It is noted that in the early stages of the literary process psychologism had a secondary role, since for the formation of psychologism a high level of social development and awareness of the value of the individual is required. The positions of psychologism in literature are intensified in the XVIII century in such a literary trend as sentimentalism. The tradition of the use of psychology by writers of sentimentalists and romantics was continued by realists. So, in the depiction of a literary hero a correlation of the external image with the description of the internal state to understand the true basis of the actions of the character is necessary. It is shown in the article that there were conditions conducive to the development of psychologism in the 19th century. The end of the 19th – the beginning of the 20th century is considered a period of general psychologisation of literature. Psychologism continues its development in the literature of the 20th century gaining a special orientation within the framework of socialist realism. The specifics of that era gave rise to a special type of literature that developed contrary to the official doctrine and was called dissident literature.